Outbreak of brainstem encephalitis associated with enterovirus-A71 in Catalonia, Spain (2016): a clinical observational study in a children's reference centre in Catalonia. (November 2017) - Casas-Alba, D.; de Sevilla, M.F.; Valero-Rello, A.; Fortuny, C.; García-García, J.-J.; Ortez, C.; Muchart, J.; Armangué, T.; Jordan, I.; Luaces, C.; Barrabeig, I.; González-Sanz, R.; et al.
Abstract: Objectives: To describe the characteristics of an outbreak of brainstem encephalitis and encephalomyelitis related to enterovirus (EV) infection in Catalonia (Spain), a setting in which these manifestations were uncommon. Methods: Clinical and microbiological data were analysed from patients with neurological symptoms associated with EV detection admitted to a reference paediatric hospital between April and June 2016. Results: Fifty-seven patients were included. Median age was 27.7 months (p25-p75 17.1–37.6). Forty-one (72%) were diagnosed with brainstem encephalitis, seven (12%) with aseptic meningitis, six (11%) with encephalitis, and three (5%) with encephalomyelitis (two out of three with cardiopulmonary failure). Fever, lethargy, and myoclonic jerks were the most common symptoms. Age younger than 12 months, higher white-blood-cell count, and higher procalcitonin levels were associated with cardiopulmonary failure. Using a PAN-EV real-time PCR, EV was detected in faeces and/or nasopharyngeal aspirate in all the patients, but it was found in cerebrospinal fluid only in patients with aseptic meningitis. EV was genotyped in 47 out of 57 and EV-A71 was identified in 40 out of 47, being the only EV type found in patients with brainstem symptoms. Most of the detected EV-A71 strains were subgenogroup C1. Intravenous immunoglobulins were used in 34 patients. Eight cases (14%) were admitted to the intensive care unit. All the patients but three, those with encephalomyelitis, showed a good clinical course and had no significant sequelae. No deaths occurred. Conclusions: The 2016 outbreak of brainstem encephalitis in Catalonia was associated with EV-A71 subgenogroup C1. Despite the clinical manifestations of serious disease, a favourable outcome was observed in the majority of patients.